Reversible magnetism switching of iron oxide nanoparticle dispersions by controlled agglomeration - Müssig, Stephan; Kuttich, Bjoern; Fidler, Florian; Haddad, Daniel; Wintzheimer, Susanne; Kraus, Tobias; Mandel, Karl (Nanoscale Advances, 2021)
The controlled agglomeration of superparamagnetic iron oxide nanoparticles (SPIONs) was used to rapidly switch their magnetic properties. Small-angle X-ray scattering (SAXS) and dynamic light scattering showed that tailored iron oxide nanoparticles with phase-changing organic ligand shells agglomerate at temperatures between 5 °C and 20 °C. We observed the concurrent change in magnetic properties using magnetic particle spectroscopy (MPS) with a temporal resolution on the order of seconds and found reversible switching of magnetic properties of SPIONs by changing their agglomeration state. The non-linear correlation between magnetization amplitude from MPS and agglomeration degree from SAXS data indicated that the agglomerates' size distribution affected magnetic properties. This journal is
CRIS-Team Scopus Importer:2021-06-04